Non-steroidal anti-inflammatory drugs(NSAIDs) and physiotherapy - a selective review - P. van der Bijl; R. de Jager; C. M.M. Nel (AOSIS, 2002)
This paper presents a selective review on the non-steroidal anti-inflammatory drugs (NSAIDs). These drugs,which form the mainstay of treatment of a variety of musculoskeletal and rheumatic conditions, may facilitate the efficacy of and compliance with physiotherapy treatment.  Their mechanisms of action, adverse effects, various routes of administration, eg systemic versus topical, and the role that these drugs may play in physiotherapy practice  are discussed.